From pulpit to digital platform: The routinization of charisma online among Indonesian ulama - Mutamakin, Mutamakin; Alahmadi, Fahd Mohana S.; Fauzan, Aris; Fannani, Bakhruddin (Center for Sociological Studies and Community Developmen, 2025)
This article investigates how Indonesian ulama construct charismatic authority on social media, examining how Weberian charisma is signaled, routinized, and scaled in digital environments. The study employs a multiple case study design, analyzing five prominent Indonesian ulama through qualitative content and platform analysis. Data from Instagram, YouTube, and X/Twitter reveal digital charisma as a carefully curated performance, signaled through strategic blending of traditional piety with modern relatability. The research demonstrates how charisma becomes routinized through consistent, platform-specific content that fosters perceived intimacy with followers, while algorithmic amplification enables unprecedented scaling beyond traditional geographical and institutional boundaries. Platform algorithms play a crucial role in both routinizing charisma through content distribution patterns and scaling it through automated recommendation systems. The study's theoretical contribution lies in synthesizing Weber's sociology of charisma with deep mediatization theory within Indonesia's distinctive pluralistic Islamic context. These findings carry significant practical implications, particularly the urgent need to integrate critical digital literacy into Islamic leadership education curricula. Understanding platform mechanics becomes essential for navigating the new religious authority landscape, while the findings also raise important questions about platform governance and algorithmic amplification of religious content in diverse societies.